Preparation method of carbon nanofiber reinforced carbon material fiber fabric

The carbon nanofibers are wrapped on the carbon material fibers through electrospinning technology and subjected to hot pressing and carbonization, which solves the problem of insufficient bonding force at the fiber interface and significantly improves the mechanical, electrical and thermal conductivity of the carbon material fiber fabric.

CN119877184AActive Publication Date: 2025-04-25DONGHUA UNIV

Patent Information

Application Number
CN202510392132.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The interface bonding force between fibers in carbon material fiber fabrics is insufficient, resulting in fiber slippage, impeded electron transport, and degradation of mechanical properties and electrical conductivity.

Method used

The carbon nanofiber membrane is evenly wrapped on the weakly twisted carbon material fiber tow through electrostatic spinning technology, forming a bridge structure and a three-dimensional network structure, improving interface bonding, and improving the density and performance of the fabric through hot pressing and carbonization treatment.

Benefits of technology

The interface bonding strength between the fibers is significantly improved, the mechanical properties, electrical conductivity and thermal conductivity of the fabric are enhanced, the gaps and defects are reduced, and the overall performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877184A_ABST
    Figure CN119877184A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon material fibers, and discloses a preparation method of a carbon nanofiber reinforced carbon material fiber fabric, which comprises the following steps: fixing a weakly twisted carbon material fiber tow on an electrostatic spinning nano yarn machine; forming a carbon nanofiber membrane by utilizing electrostatic spinning, uniformly wrapping the carbon nanofiber membrane on a carbon material fiber bundle subjected to weak twisting, then rolling into a shaft, then weaving the rolled fibers into a fabric, and sequentially performing hot pressing and carbonization treatment on the fabric to prepare a carbon nanofiber reinforced carbon material fiber fabric; the weak twisting means that the twisting degree is 5-13 twists per meter. According to the invention, the carbon nanofiber is coated on the carbon material fiber, so that the interface bonding strength between the nanofiber and the carbon material fiber is improved, and then the fabric prepared from the carbon nanofiber is subjected to hot pressing and carbonization treatment, so that the mechanical property, the electrical conductivity and the heat-conducting property of the fabric are further improved; therefore, the composite material has a huge application prospect in the fields of high-performance composite materials, intelligent textiles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon material fibers and relates to a method for preparing carbon nanofiber reinforced carbon material fiber fabric. Background Art

[0002] Carbon fiber, with its excellent mechanical properties, high specific surface area and good conductivity, shows great application potential in the fields of energy, environment and composite materials. However, despite the broad prospects, fabrics woven from carbon fiber are not perfect and still face some problems that need to be solved. Among them, the defects between carbon fiber fibers have become the key factor restricting the improvement of the overall performance of fabrics. The root cause of these defects is that the interfacial bonding force between fibers is obviously insufficient. Specifically, the surface of graphene sheets is smooth, which makes the physical contact area between fibers relatively small, thus leading to the weakening of interfacial bonding force. Similarly, carbon fiber itself has a smooth surface and is chemically inert, and its interfacial bonding mainly relies on physical forces, such as van der Waals forces, which is relatively weak. In addition, carbon nanotubes also have a smooth surface, and the interfacial bonding force between fibers is also relatively weak. The consequence of low interfacial bonding strength is that slippage is easy to occur between fibers, which not only hinders the effective transmission of electrons between fibers, but also reduces the tensile strength and conductivity of the fabric.

[0003] Therefore, in the process of weaving carbon fiber into fabric, a large number of voids will be formed due to the staggered arrangement and stacking of the fibers and the weak interfacial bonding force between the carbon fiber fibers. These voids not only destroy the structural continuity of the fabric, but also seriously affect its mechanical properties and functionality. In addition, the voids will lead to uneven stress distribution, which is easy to cause local stress concentration and crack propagation under the action of external loads, significantly reducing the tensile strength, toughness and fatigue resistance of the fabric. At the same time, the presence of voids will also reduce the effective contact area between fibers, reduce friction and mechanical interlocking, and further weaken the overall mechanical properties of the fabric. In terms of electrical and thermal conductivity, voids will also interrupt the electron transmission path, increase the interface contact resistance, and reduce the electrical conductivity; at the same time, voids also hinder the effective transfer of heat and reduce thermal conductivity.

[0004] In order to further improve the performance of fiber fabrics, existing technologies usually use sizing agents or resins to modify them, but these non-conductive or low-thermal-conductivity organic layers will hinder the electron transfer and heat transfer between fibers, reducing electrical and thermal conductivity. In addition, the introduction of sizing agents or resins may also form an uneven covering layer, resulting in further degradation of performance in local areas, and when the sizing agents or resins are removed, the fiber surface will also be damaged.

[0005] For example, the patent application with application publication number CN119433988A discloses an interface-enhanced carbon fiber sizing agent and its preparation method and application method, which can effectively enhance the bonding ability between the sizing agent and the carbon fiber and the matrix resin, thereby effectively improving the interface performance of the carbon fiber composite material. However, as an organic material, the sizing agent will form an insulating layer on the fiber surface, hindering the transmission of electrons and phonons, thereby reducing the electrical conductivity and thermal conductivity of the fiber.

[0006] Although there are also existing technologies that use electrochemical deposition technology to introduce functional coatings to enhance fiber performance, the process may cause chemical corrosion or oxidation on the fiber surface, especially under high voltage or long-term deposition conditions. For example, the literature (Electrodeposited carbon nanostructured nickel composite coatings: A review[J].Heliyon, 10(8):e26051[2025-02-28].DOI:10.1016 / j.heliyon.2024.e26051.) mentions that the use of electrochemical deposition to deposit graphene oxide (GO) on the surface of carbon fiber can significantly improve the interfacial bonding strength between carbon fiber and epoxy resin matrix, while improving the mechanical properties of the composite material. However, the electrochemical deposition method will cause chemical corrosion or oxidation on the fiber surface, destroy the structure, and lead to a decrease in the mechanical, electrical, and thermal conductivity of the fiber.

[0007] Therefore, it is of great significance to study a method for preparing carbon nanofiber reinforced carbon material fiber fabric to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and to provide a method for preparing a carbon nanofiber reinforced carbon material fiber fabric.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A preparation method of carbon nanofiber reinforced carbon material fiber fabric, the method comprises: fixing a weakly twisted carbon material fiber bundle on an electrostatic spinning nano yarn machine (the electrostatic spinning nano yarn machine is a prior art, and the weakly twisted carbon material fiber bundle is fixed in a specific manner as follows: manually pulling out the end of the carbon material fiber bundle on the spinning reel from the conical yarn guide on the left, adjusting the tension of the pulled fiber bundle by a control device, and then leading the bundle to the guide hole on the right, fixing it on the clamp of a wire collection device, and controlling the winding speed of the bundle by a motor drive system), forming a carbon nanofiber film by electrostatic spinning and uniformly wrapping it on the weakly twisted carbon material fiber bundle, thereby realizing protection and weavability of the surface of the carbon material fiber bundle, improving wear resistance and tensile properties of the composite fiber, and then rolling it into a shaft, and then weaving the rolled fiber bundle into a fabric, and performing hot pressing and carbonization treatment on the fabric in sequence to obtain a carbon nanofiber reinforced carbon material fiber fabric;

[0011] Weak twisting refers to a twist of 5 to 13 twists / meter. Twist refers to the number of twists of the yarn per unit length, usually expressed in twists / meter (tpm) or twists / inch (tpi). The twist of weak twisting is usually 20 to 50% lower than that of standard twisting, and the present invention is limited to 5 to 13 tpm. Weak twisting can make the weak nodes of the carbon material fiber become tight and mutually embraced to prevent slippage or breakage, thereby making the strength of the fiber uniform;

[0012] After spinning on the surface of the carbon material fiber to form carbon nanofibers, the surface microstructure of the carbon material fiber can be significantly improved, making it rougher and having active sites. This structural change helps to improve the interface bonding strength between the carbon nanofibers and the carbon material fibers.

[0013] In the process of weaving carbon fiber into cloth, due to the staggered arrangement and stacking mode between fibers, a large number of void structures are formed between fibers. These voids not only destroy the structural continuity of the fabric, but also seriously affect its mechanical properties and functionality. Carbon nanofibers have extremely high aspect ratio and flexibility. The present invention can form a continuous bridge structure between fiber overlap points by coating the carbon nanofibers obtained by electrospinning on the carbon material fiber bundle. Through the expansion and connection of the bridge structure, a three-dimensional network structure is formed, thereby effectively transmitting and dispersing external loads and reducing stress concentration. This bridge structure can also improve the density of the fabric, and can also enhance the mechanical interlocking effect between fibers, thereby improving the overall mechanical properties (such as tensile strength and fatigue resistance) of the fabric. And carbon nanofibers have excellent electrical conductivity and thermal conductivity, and can form a continuous conductive and thermal conductive channel between fiber overlap points, which can not only improve the electrical conductivity of the fabric, but also enhance the thermal conductivity of the fabric.

[0014] After the rolled fibers are woven into fabrics, they are first heat-pressed to reduce voids and defects inside the fabrics and improve the overall density and mechanical properties of the material. They are then carbonized to eliminate non-carbon elements in the fibers and form a highly ordered carbon structure through structural rearrangement and graphitization at high temperatures. The mechanical, electrical and thermal properties of the fabrics are also further improved. The porous interface in the fibers can penetrate the resin to improve the bonding strength with the resin.

[0015] As the preferred technical solution:

[0016] In the method for preparing a carbon nanofiber reinforced carbon material fiber fabric as described above, the carbon material fiber is graphene fiber, carbon nanotube fiber or carbon fiber.

[0017] In the method for preparing a carbon nanofiber reinforced carbon material fiber fabric as described above, the spinning solution used in electrospinning is prepared by adding a catalyst to a polyacrylonitrile (PAN) solution, an asphalt solution or a viscose fiber solution, and the catalyst is ZnCl 2 、FeCl 3 and one or more of nickel powder.

[0018] In the method for preparing a carbon nanofiber reinforced carbon material fiber fabric as described above, the concentration of the polyacrylonitrile solution is 10~20wt%, the concentration of the asphalt solution is 10~20wt%, the concentration of the viscose fiber solution is 10~20wt%, and the amount of the catalyst used is 0.1~5wt% of the polyacrylonitrile, asphalt or viscose fiber.

[0019] The preparation method of a carbon nanofiber reinforced carbon material fiber fabric as described above, the electrospinning process parameters are: voltage 10~30 kV, the distance between the spinneret and the collecting device (i.e., the electrospinning nano yarn machine) is 10~20 cm, the injection pump propulsion rate is 0.5~1.5mL / h, the fiber reel winding rate is 10~40 cm / min, the drying temperature is 60~100°C, and the spinning time is 1~8 h.

[0020] In the method for preparing a carbon nanofiber reinforced carbon material fiber fabric as described above, the thickness of the carbon nanofiber membrane is 27-30 nm, and the average fiber diameter in the carbon nanofiber membrane is 240-260 nm.

[0021] In the preparation method of the carbon nanofiber reinforced carbon material fiber fabric as described above, the hot pressing temperature is 200~300°C, the pressure is 10~50MPa, and the time is 10~30min, which can reduce the gaps and defects inside the fabric and improve the overall density and mechanical properties of the material.

[0022] In the preparation method of a carbon nanofiber reinforced carbon material fiber fabric as described above, the carbonization treatment temperature is 1300~1600℃ and the time is 50~80min, which can rearrange the carbon atoms in the fiber to form a more stable graphite structure, significantly improving the mechanical, electrical and thermal conductivity of the fabric.

[0023] In the method for preparing the carbon nanofiber reinforced carbon material fiber fabric as described above, the weaving method is weaving or knitting.

[0024] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric as described in any one of the above items, wherein compared with a comparative sample, the electrical conductivity of the carbon nanofiber reinforced carbon material fiber fabric is increased by 35-100%, the thermal conductivity is increased by 25-95%, the tensile strength is increased by 80-200%, and the bending fatigue life is increased by 25-80%;

[0025] The preparation of the control sample is compared with the preparation of the carbon nanofiber reinforced carbon material fiber fabric, and the only difference is that the material used for weaving is the untreated carbon material fiber bundle.

[0026] Beneficial effects:

[0027] (1) The present invention forms a continuous bridging structure between the fiber overlap points by coating the carbon nanofibers obtained by electrospinning on the carbon material fibers, thereby forming a three-dimensional network structure between the fiber overlap points, thereby effectively transmitting and dispersing the external load and reducing stress concentration. This bridging structure can also improve the density of the fabric and enhance the mechanical interlocking effect between the fibers, thereby improving the overall mechanical properties of the fabric and making it have good weavability; in addition, after spinning the carbon nanofibers on the surface of the carbon material fibers, the surface microstructure of the carbon material fibers can be significantly improved, making them rougher and having active sites. This structural change helps to improve the interface bonding strength between the nanofibers and the carbon material fibers.

[0028] (2) The present invention first performs a heat pressing treatment on the fabric to reduce the voids and defects inside the fabric and improve the overall density and mechanical properties of the material. Then, the fabric is subjected to a carbonization treatment. Through the structural rearrangement and graphitization process at high temperature, not only can the non-carbon elements in the fiber be eliminated to form a highly ordered carbon structure, but the mechanical properties, electrical conductivity and thermal conductivity of the fabric can also be further improved. In addition, the porous interface existing in the fiber can penetrate the resin to improve the bonding strength with the resin.

[0029] (3) The carbon nanofiber reinforced carbon material fiber fabric prepared by the present invention has excellent mechanical properties, thermal conductivity and electrical conductivity, which makes it show great application prospects in the fields of high-performance composite materials, smart textiles, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the working process of the electrospinning nano-spinning machine used in the present invention;

[0031] Figure 2 This is a schematic diagram of the present invention before the fabric is subjected to heat pressing and carbonization treatment;

[0032] Figure 3 This is a schematic diagram of the present invention after the fabric is subjected to heat pressing and carbonization treatment;

[0033] In the figure, 1-filament output shaft, 2-weakly twisted carbon material fiber bundle, 3-motor I, 4-conical yarn guide, 5-spinneret, 6-carbon material fiber bundle wrapped with nanofiber membrane, 7-guide hole, 8-filament collection shaft, 9-motor II. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.

[0036] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0037] Conductivity of fiber: The rolled fiber bundle in each embodiment is used as a sample, and then the sample is laid flat on an insulating PET film, and the two ends are fixed with conductive double-sided tape to ensure that the contact section between the sample and the four-probe is straight and without bending. In the fiber test mode of the four-probe conductivity tester, the probe is pressed down to the sample surface, and then a current of 10μA is applied through the four-probe conductivity tester, and the voltage value V is read, and the resistance value R=V / I, and then the conductivity of the sample is calculated according to the measured data, and the calculation formula is: Conductivity=4l / (R⋅πd 2 ), where l is the probe distance (1.59 mm) and d is the diameter of the sample.

[0038] Thermal conductivity of fiber: The rolled fiber bundles in each embodiment were used as samples, and the thermal conductivity of the samples was tested according to the Q / 110000 BH008-2018 standard.

[0039] Tensile strength of fiber: The rolled fiber obtained in each embodiment was used as a sample, and the sample was tested using an electronic universal material testing machine (manufacturer: Instron; model: 34FM-100 / 300). Then, the tensile strength (unit: MPa) was obtained based on the measured data. The calculation formula is: Tensile strength = F max / A,F max is the maximum load that the sample bears during the stretching process (unit: N), and A is the cross-sectional area of ​​the sample (unit: mm²).

[0040] Bending fatigue life of fiber: The rolled fibers prepared in each embodiment were used as samples, and then the samples were cut into 5 cm lengths and their diameters were measured. The samples were then fixed in the fixture of a bending fatigue testing machine (manufacturer: Shanghai Zhongchen Digital Technology Equipment; model: JWQ06). After ensuring good contact between the sample and the fixture, the position of the fixture was adjusted so that the sample was at a predetermined bending angle (90°) and the bending frequency was set to 5 Hz. The bending fatigue testing machine was then started to apply repeated bending loads until the fiber broke, and the number of cycles when the fiber failed was recorded, which was the bending fatigue life.

[0041] Conductivity of fabric: The carbon nanofiber reinforced carbon material fiber fabrics prepared in each embodiment and the control sample were cut into 20 mm × 20 mm sizes, and then the cut fabrics were used as samples for testing. The specific process was as follows: first, the sample was laid flat on the test bench, and the edge was fixed with a transparent pressing plate (to prevent wrinkling). Then, in the fabric test mode of the four-probe conductivity tester, the probe contacted the surface of the sample with a pressure of 50 mN, and then a current of 10 mA was applied through the four-probe conductivity tester to obtain the surface resistance. (i.e. sheet resistance, unit is Ω / sq), and then calculate the conductivity of the sample (unit is S / m) based on the measured data. The calculation formula is: Conductivity = , where t is the thickness of the sample.

[0042] Thermal conductivity of fabric: The carbon nanofiber reinforced carbon material fiber fabric prepared in each embodiment and the control sample were used as samples, and then the samples were tested according to GB / T 8722-2019 "Determination of thermal conductivity of carbon materials" standard. Based on the flash method, the thermal diffusion coefficient α (in m² / s) of the fabric was tested, and then the specific heat capacity c of the sample was measured by DSC. p (unit: J / (kg·K)), the density of the sample is measured using GB / T 4668-1995 "Determination of density of woven fabrics", and then the thermal conductivity λ (unit: W / (m·K)) is calculated using the formula: λ=α⋅c p ⋅ρ, where ρ is the density.

[0043] Tensile strength of fabric: The carbon nanofiber reinforced carbon material fiber fabric prepared in each embodiment and the control sample were used as samples, and then the samples were tested according to ASTM D5035-11 (2020) "Breaking Strength and Elongation of Textile Fabrics (Strip Method)" standard to obtain the maximum breaking strength (N), and then the tensile strength (MPa) was calculated based on the obtained data. The calculation formula is: Tensile strength = Maximum breaking strength (N) / (effective width of the sample (ie, clamping width) × fabric thickness (unit: mm) 2 )).

[0044] Bending fatigue life of fabric: The carbon nanofiber reinforced carbon material fiber fabrics and the control samples prepared in each embodiment were cut into standard sizes (25 mm×50 mm) as samples and tested using a dynamic mechanical analyzer. The specific process is as follows: using a three-point bending mode, the sample is first placed horizontally between two fixed support points (span L=40 mm), and then the maximum allowable bending angle of the sample is determined through a preliminary experiment (the sample is quasi-statically bent until fracture to obtain δmax, δcyclic=0.5×δmax is set, and converted to a bending angle θ=10°), the cyclic bending angle is determined to be 10°, and then the three-point bending stress is calculated (the calculation formula for the three-point bending stress is: three-point bending stress=3FL / 2bh 2 , where F is the loading load (N), which is given in real time by the test software, L is the span, b is the sample width (i.e. 25 mm), and h is the sample thickness (in μm). Then, the displacement control mode is selected, and a vertical downward periodic load is applied at the center of the two fixed support points through the movable loading head (i.e., the loading head moves up and down in a sinusoidal wave form with a frequency of 1 Hz). When the test is started, the load-displacement curve is monitored in real time until the load drops to the sample fracture. At the same time, the number of cycles from the initial loading to the complete fracture of the sample is recorded, which is the bending fatigue life of the fabric.

[0045] Example 1

[0046] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, comprising the following steps:

[0047] (1) Preparation of raw materials;

[0048] Carbon fiber tow: composed of 600 graphene fiber monofilaments (manufacturer: Hangzhou Gaoxi Technology Co., Ltd., brand name: GK-3000);

[0049] Catalyst: ZnCl 2 ;

[0050] Polyacrylonitrile (PAN) solution: concentration is 10wt%, solvent is N,N-dimethylformamide (DMF), polyacrylonitrile is from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number is 25014-41-9, product number is P823208;

[0051] (2) preparing spinning solution;

[0052] The catalyst is added to a polyacrylonitrile (PAN) solution to prepare a spinning solution; wherein the amount of the catalyst is 0.1wt% of the polyacrylonitrile (PAN);

[0053] (3) After the carbon fiber tow is weakly twisted on the twisting machine, Figure 1 As shown, a weakly twisted carbon material fiber bundle 2 is placed on a filament output shaft 1, and after the conical yarn guide 4 and the yarn collection shaft 8 are started by motors I 3 and II 9, the weakly twisted carbon material fiber bundle 2 passes through the conical yarn guide 4, and then, by means of electrospinning, the spinning solution prepared in step (2) is ejected through a spinneret 5 to form a nanofiber membrane and uniformly wrapped on the weakly twisted carbon material fiber bundle 2, thereby obtaining a carbon material fiber bundle 6 wrapped with a nanofiber membrane, which is then rolled into a shaft by a yarn collection shaft 8 after passing through a guide hole 7; wherein the thickness of the carbon nanofiber membrane is 27 nm, the average diameter of the fibers in the carbon nanofiber membrane is 240 nm, and the twist degree of the weak twist is 5 twists / m;

[0054] The electrospinning process parameters were: voltage 10 kV, distance between spinneret and collecting device 10 cm, syringe pump advancement rate 0.5 mL / h, fiber reel collection rate 10 cm / min, drying temperature 60 °C, spinning time 1 h;

[0055] The diameter of the fiber bundle after winding is 0.5mm, the electrical conductivity is 100S / m, the thermal conductivity is 50W / (m·K), the tensile strength is 100MPa, and the bending fatigue life is 1000 times;

[0056] (4) First, the wound fiber tow is arranged into yarn, and then twisted at a twist of 100 twists / m. Then, the yarn is introduced into the weaving point of the weaving machine, and weaved at a speed of 50 revolutions / minute. Finally, the woven fabric is wound up; wherein, the pitch is adjusted to 1 mm, the warp density is 20 strands / cm, the weft density is 15 strands / cm, and the tension is 5N;

[0057] (5) The fabric is subjected to heat pressing and carbonization treatment in sequence (the fabric is subjected to heat pressing and carbonization treatment before and after the treatment). Figure 2 , Figure 3 As shown), carbon nanofiber reinforced carbon material fiber fabric was obtained; wherein, the hot pressing temperature was 200°C, the pressure was 10MPa, the time was 10min, and the carbonization treatment temperature was 1300°C, and the time was 50min.

[0058] The thickness of the carbon nanofiber reinforced carbon material fiber fabric finally obtained is 0.5mm, the electrical conductivity is 135S / m, the thermal conductivity is 62.5W / (m·K), the tensile strength is 180MPa, and the bending fatigue life is 1300 times;

[0059] Then, a comparative sample is prepared, and the preparation method thereof is basically the same as steps (1) to (5), except that the carbon material fiber bundle in step (1) is replaced by the fiber bundle rolled up in step (3);

[0060] Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 35%, thermal conductivity increased by 25%, tensile strength increased by 80%, and bending fatigue life increased by 25%.

[0061] Example 2

[0062] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, comprising the following steps:

[0063] (1) Preparation of raw materials;

[0064] Carbon material fiber tow: composed of 1200 carbon nanotube fiber monofilaments (manufacturer is Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number 100592);

[0065] Catalyst: FeCl 3 ;

[0066] Asphalt solution: concentration is 15wt%, the solvent is acetone (manufacturer is Merck Chemical Technology (Shanghai) Co., Ltd., CAS No. 67-64-1), the manufacturer of asphalt is Shanghai Yien Chemical Technology Co., Ltd., the brand is R139415;

[0067] (2) preparing spinning solution;

[0068] The catalyst is added to the asphalt solution to prepare a spinning solution, wherein the amount of the catalyst is 3wt% of the asphalt;

[0069] (3) After weakly twisting the carbon material fiber bundle on a twisting machine, the weakly twisted carbon material fiber bundle is fixed on an electrospinning nano yarn machine, and then the spinning solution prepared in step (2) is used to form a carbon nanofiber membrane by electrospinning and uniformly wrap it on the weakly twisted carbon material fiber bundle, and then it is rolled into a shaft; wherein the thickness of the carbon nanofiber membrane is 28nm, the average fiber diameter in the carbon nanofiber membrane is 252nm, and the twist degree of the weak twist is 9 twists / m;

[0070] The electrospinning process parameters were: voltage 20 kV, distance between spinneret and collecting device 15 cm, syringe pump advancement rate 1 mL / h, fiber reel collection rate 21 cm / min, drying temperature 80 °C, spinning time 5 h;

[0071] The diameter of the fiber bundle after winding is 0.8mm, the electrical conductivity is 260S / m, the thermal conductivity is 60W / (m·K), the tensile strength is 200MPa, and the bending fatigue life is 1500 times;

[0072] (4) The wound fiber tow is first arranged into yarn, and then twisted at a twist of 200 twists / m, and then the yarn is formed into coils using a knitting machine, and the coils are interlaced to form a fabric at a speed of 200 revolutions / minute, and finally the woven fabric is wound up; wherein the number of needles (i.e., needle density) is 12 needles / inch, and the tension is 13N;

[0073] (5) The fabric is subjected to hot pressing and carbonization treatment in sequence to obtain a carbon nanofiber reinforced carbon material fiber fabric; wherein the hot pressing temperature is 240°C, the pressure is 25 MPa, and the time is 20 min; the carbonization temperature is 1460°C, and the time is 65 min.

[0074] The thickness of the carbon nanofiber reinforced carbon material fiber fabric finally obtained is 0.7mm, the electrical conductivity is 435S / m, the thermal conductivity is 96W / (m·K), the tensile strength is 680MPa, and the bending fatigue life is 2295 times;

[0075] Then, a comparative sample is prepared, and the preparation method thereof is basically the same as steps (1) to (5), except that the carbon material fiber bundle in step (1) is replaced by the fiber bundle rolled up in step (3);

[0076] Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 67.5%, thermal conductivity increased by 60%, tensile strength increased by 140%, and bending fatigue life increased by 53%.

[0077] Example 3

[0078] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, comprising the following steps:

[0079] (1) Preparation of raw materials;

[0080] Carbon fiber tow: composed of 2100 carbon fiber monofilaments (manufacturer is Yancheng Xiangsheng Carbon Fiber Technology Co., Ltd., brand is carbon fiber filament, specification is 12K);

[0081] Catalyst: nickel powder;

[0082] Viscose fiber solution: concentration is 20wt%, the solvent is acetone (manufacturer is Merck Chemical Technology (Shanghai) Co., Ltd., CAS No. 67-64-1), the manufacturer of viscose fiber is Xinxiang Qihang Textile Raw Materials Co., Ltd., specification is 300D / 50F;

[0083] (2) preparing spinning solution;

[0084] The catalyst is added to the viscose fiber solution to prepare a spinning solution, wherein the amount of the catalyst is 5wt% of the viscose fiber;

[0085] (3) After weakly twisting the carbon material fiber bundle on a twisting machine, the weakly twisted carbon material fiber bundle is fixed on an electrospinning nano yarn machine, and then the spinning solution prepared in step (2) is used to form a carbon nanofiber membrane by electrospinning and uniformly wrap it on the weakly twisted carbon material fiber bundle, and then it is rolled into a shaft; wherein the thickness of the carbon nanofiber membrane is 30nm, the average fiber diameter in the carbon nanofiber membrane is 260nm, and the twist degree of weak twisting is 13 twists / meter;

[0086] The electrospinning process parameters were: voltage 30 kV, distance between spinneret and collecting device 20 cm, syringe pump advancement rate 1.5 mL / h, fiber reel collection rate 40 cm / min, drying temperature 100 °C, spinning time 8 h;

[0087] The diameter of the fiber bundle after winding is 1mm, the electrical conductivity is 420S / m, the thermal conductivity is 120W / (m·K), the tensile strength is 600MPa, and the bending fatigue life is 1900 times;

[0088] (4) First, the wound fiber tow is arranged into yarn, and then twisted at a twist of 300 twists / m. Then, the yarn is introduced into the weaving point of the weaving machine, and weaved at a speed of 100 revolutions / minute. Finally, the woven fabric is wound up; wherein, the pitch is adjusted to 5 mm, the warp density is 40 strands / cm, the weft density is 35 strands / cm, and the tension is 20N;

[0089] (5) The fabric is subjected to hot pressing and carbonization treatment in sequence to obtain carbon nanofiber reinforced carbon material fiber fabric; wherein the hot pressing temperature is 300°C, the pressure is 50 MPa, and the time is 30 min; the carbonization temperature is 1600°C, and the time is 80 min.

[0090] The thickness of the carbon nanofiber reinforced carbon material fiber fabric finally obtained is 1mm, the electrical conductivity is 840S / m, the thermal conductivity is 234W / (m·K), the tensile strength is 1200MPa, and the bending fatigue life is 3600 times;

[0091] Then, a comparative sample is prepared, and the preparation method thereof is basically the same as steps (1) to (5), except that the carbon material fiber bundle in step (1) is replaced by the fiber bundle rolled up in step (3);

[0092] Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 100%, the thermal conductivity increased by 95%, the tensile strength increased by 200%, and the bending fatigue life increased by 80%.

[0093] Example 4

[0094] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, comprising the following steps:

[0095] (1) Preparation of raw materials;

[0096] Carbon fiber tow: composed of 1,700 carbon fiber monofilaments (manufacturer: Yancheng Xiangsheng Carbon Fiber Technology Co., Ltd., brand: carbon fiber filament, specification: 12K);

[0097] Catalyst: ZnCl with a mass ratio of 1:1 2 and FeCl 3 composition;

[0098] Polyacrylonitrile (PAN) solution: concentration is 16wt%, solvent is N,N-dimethylformamide (DMF), polyacrylonitrile is from Shanghai MacLean Biochemical Technology Co., Ltd., CAS number is 25014-41-9, product number is P823208;

[0099] (2) preparing spinning solution;

[0100] The catalyst is added to a polyacrylonitrile (PAN) solution to prepare a spinning solution; wherein the amount of the catalyst is 2wt% of the polyacrylonitrile (PAN);

[0101] (3) After weakly twisting the carbon material fiber bundle on a twisting machine, the weakly twisted carbon material fiber bundle is fixed on an electrospinning nano yarn machine, and then the spinning solution prepared in step (2) is used to form a carbon nanofiber membrane by electrospinning and uniformly wrap it on the weakly twisted carbon material fiber bundle, and then rolled into a shaft; wherein the thickness of the carbon nanofiber membrane is 28nm, the average fiber diameter in the carbon nanofiber membrane is 245nm, and the twist degree of the weak twist is 10 twists / meter;

[0102] The electrospinning process parameters were: voltage 20 kV, distance between spinneret and collecting device 16 cm, syringe pump advancement rate 0.8 mL / h, fiber reel collection rate 16 cm / min, drying temperature 70 °C, spinning time 6 h;

[0103] The diameter of the fiber tow after winding is 0.6mm, the electrical conductivity is 320S / m, the thermal conductivity is 100W / (m·K), the tensile strength is 500MPa, and the bending fatigue life is 1680 times;

[0104] (4) First, the wound fiber tow is arranged into yarn, and then twisted at a twist of 220 twists / m. Then, the yarn is introduced into the weaving point of the weaving machine and weaved at a speed of 60 revolutions / minute. Finally, the woven fabric is wound up. Among them, the pitch is adjusted to 2 mm, the warp density is 25 strands / cm, the weft density is 20 strands / cm, and the tension is 13N.

[0105] (5) The fabric is subjected to hot pressing and carbonization treatment in sequence to obtain a carbon nanofiber reinforced carbon material fiber fabric; wherein the hot pressing temperature is 250°C, the pressure is 30 MPa, and the time is 15 min; the carbonization temperature is 1500°C, and the time is 70 min.

[0106] The thickness of the carbon nanofiber reinforced carbon material fiber fabric finally obtained is 0.6mm, the electrical conductivity is 560S / m, the thermal conductivity is 160W / (m·K), the tensile strength is 900MPa, and the bending fatigue life is 2800 times;

[0107] Then, a comparative sample is prepared, and the preparation method thereof is basically the same as steps (1) to (5), except that the carbon material fiber bundle in step (1) is replaced by the fiber bundle rolled up in step (3);

[0108] Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 75%, thermal conductivity increased by 60%, tensile strength increased by 80%, and bending fatigue life increased by 66%.

[0109] Example 5

[0110] A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, comprising the following steps:

[0111] (1) Preparation of raw materials;

[0112] Carbon fiber tow: composed of 1,300 graphene fiber monofilaments (manufacturer: Hangzhou Gaoxi Technology Co., Ltd., brand name: GK-3000);

[0113] Catalyst: nickel powder and FeCl in a mass ratio of 1:1 3 composition;

[0114] Viscose fiber solution: concentration is 14wt%, solvent is acetone (manufacturer is Merck Chemical Technology (Shanghai) Co., Ltd., CAS No. 67-64-1), manufacturer of viscose fiber is Xinxiang Qihang Textile Raw Materials Co., Ltd., specification is 300D / 50F;

[0115] (2) preparing spinning solution;

[0116] The catalyst is added to the viscose fiber solution to prepare a spinning solution, wherein the amount of the catalyst is 3.5wt% of the viscose fiber;

[0117] (3) After weakly twisting the carbon material fiber bundle on a twisting machine, the weakly twisted carbon material fiber bundle is fixed on an electrospinning nano yarn machine, and then the spinning solution prepared in step (2) is used to form a carbon nanofiber membrane by electrospinning and uniformly wrap it on the weakly twisted carbon material fiber bundle, and then it is rolled into a shaft; wherein the thickness of the carbon nanofiber membrane is 29nm, the average fiber diameter in the carbon nanofiber membrane is 255nm, and the twist degree of the weak twist is 10 twists / meter;

[0118] The electrospinning process parameters were: voltage 20 kV, distance between spinneret and collecting device 18 cm, syringe pump advancement rate 1.2 mL / h, fiber reel collection rate 30 cm / min, drying temperature 90 °C, spinning time 6 h;

[0119] The diameter of the fiber tow after winding is 0.7 mm, the electrical conductivity is 400 S / m, the thermal conductivity is 95 W / (m·K), the tensile strength is 320 MPa, and the bending fatigue life is 1530 times;

[0120] (4) The wound fiber bundles are first arranged into yarns, and then twisted at a twist of 260 twists / m. The yarns are then formed into coils using a knitting machine, and the coils are interlaced to form a fabric at a speed of 240 revolutions / minute. Finally, the woven fabric is wound up; wherein the number of needles (i.e., needle density) is 10 needles / inch, and the tension is 17N;

[0121] (5) The fabric is subjected to hot pressing and carbonization treatment in sequence to obtain carbon nanofiber reinforced carbon material fiber fabric; wherein the hot pressing temperature is 270°C, the pressure is 40 MPa, and the time is 15 min; the carbonization temperature is 1400°C, and the time is 60 min.

[0122] The thickness of the carbon nanofiber reinforced carbon material fiber fabric finally obtained is 0.8mm, the electrical conductivity is 630S / m, the thermal conductivity is 180W / (m·K), the tensile strength is 800MPa, and the bending fatigue life is 2200 times;

[0123] Then, a comparative sample is prepared, and the preparation method thereof is basically the same as steps (1) to (5), except that the carbon material fiber bundle in step (1) is replaced by the fiber bundle rolled up in step (3);

[0124] Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 57.5%, the thermal conductivity increased by 89.48%, the tensile strength increased by 150%, and the bending fatigue life increased by 44%.

Claims

1. A method for preparing a carbon nanofiber reinforced carbon material fiber fabric, characterized in that: The weakly twisted carbon fiber bundle is fixed on an electrospinning nano yarn machine, a carbon nanofiber film is formed by electrospinning and uniformly wrapped on the weakly twisted carbon fiber bundle, and then rolled into a shaft, and then the rolled fiber bundle is woven into a fabric, and the fabric is sequentially hot-pressed and carbonized to obtain a carbon nanofiber reinforced carbon fiber fabric; Weak twisting refers to a twist of 5 to 13 twists per meter.

2. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 1, characterized in that: The carbon material fiber is graphene fiber, carbon nanotube fiber or carbon fiber.

3. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 1, characterized in that: The spinning solution used in electrospinning is prepared by adding a catalyst to a polyacrylonitrile solution, an asphalt solution or a viscose fiber solution, and the catalyst is one or more of ZnCl2, FeCl3 and nickel powder.

4. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 3, characterized in that: The concentration of the polyacrylonitrile solution is 10-20wt%, the concentration of the asphalt solution is 10-20wt%, the concentration of the viscose fiber solution is 10-20wt%, and the amount of the catalyst used is 0.1-5wt% of the polyacrylonitrile, asphalt or viscose fiber.

5. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 4, characterized in that: The electrospinning process parameters are as follows: voltage 10~30 kV, distance between spinneret and collecting device 10~20 cm, syringe pump propulsion rate 0.5~1.5 mL / h, fiber reel winding rate 10~40 cm / min, drying temperature 60~100 ℃, spinning time 1~8 h.

6. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 5, characterized in that: The thickness of the carbon nanofiber membrane is 27~30 nm, and the average fiber diameter in the carbon nanofiber membrane is 240~260 nm.

7. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 1, characterized in that: The hot pressing temperature is 200~300℃, the pressure is 10~50MPa, and the time is 10~30min.

8. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 7, characterized in that: The temperature of carbonization treatment is 1300~1600℃ and the time is 50~80min.

9. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to claim 1, characterized in that: The weaving method is braiding or knitting.

10. The method for preparing a carbon nanofiber reinforced carbon material fiber fabric according to any one of claims 1 to 9, characterized in that: Compared with the control sample, the electrical conductivity of carbon nanofiber reinforced carbon material fiber fabric increased by 35~100%, the thermal conductivity increased by 25~95%, the tensile strength increased by 80~200%, and the bending fatigue life increased by 25~80%; The preparation of the comparative sample is compared with the preparation of the carbon nanofiber reinforced carbon material fiber fabric, and the only difference is that the material used for weaving is the carbon material fiber bundle.

Citation Information

Patent Citations

  • Interface-enhanced carbon fiber sizing agent as well as preparation method and application method thereof

    CN119433988A

  • Nanometer fiber yarn and preparation method thereof

    CN105970309A

  • Novel method for preparing carbon nanotube / carbon nanofiber composite membranes

    CN110616561A

  • Carbon nanotube fiber hybrid fabric, preparation method thereof and reinforced composite material

    CN111705391A

  • Flexible carbon nanofiber membrane with orientation structure and preparation method thereof

    CN114318664A

Cited By

  • High-durability micro-nano structure carbon-ceramic composite material brake disc and preparation method thereof

    CN120736915A

  • High-conductivity carbon fiber material, preparation method thereof and application of high-conductivity carbon fiber material in bipolar plate of flow battery

    CN121023808A

  • Stretchable elastic carbon nanofiber membrane material and preparation method thereof

    CN122013441A